Personal exposure to polycyclic aromatic hydrocarbons in Appalachian mining communities. (February 2020) - Hendryx, Michael; Wang, Shaorui; Romanak, Kevin A.; Salamova, Amina; Venier, Marta
Abstract: Coal mining activities may increase residential exposure to polycyclic aromatic hydrocarbons (PAHs), but personal PAH exposures have not been studied in mining areas. We used silicone wristbands as passive personal samplers to estimate PAH exposures in coal mining communities in Central Appalachia in the United States. Adults (N = 101) wore wristbands for one week; 51 resided in communities within approximately three miles of surface mining sites, and 50 resided 10 or more miles from mining sites. Passive indoor polyurethane foam (PUF) sampling was conducted in residents' homes, and a sample of 16 outdoor PUF samples were also collected. Nine PAH congeners were commonly detected in wristbands (mean ± standard deviation), including phenanthrene (50.2 ± 68.7 ng/g), benz[a]anthracene (20.2 ± 58.2 ng/g), fluoranthene (19.4 ± 24.1 ng/g) and pyrene (15.2 ± 18.2 ng/g). Controlling for participant characteristics and season, participants living closer to mining sites had significantly higher levels of phenanthrene, fluorene, fluoranthene, pyrene and ∑PAHs in wristbands compared to participants living farther from mining. Indoor air showed no significant group differences except for pyrene, but outdoor air showed significant or marginally significant differences for phenanthrene, fluorene, pyrene and ∑PAHs. The results suggest that mining community residents face exposure to outdoor mining-related pollutants, and demonstrate that personal silicone wristbands can be deployed as effective passive sampling devices. Graphical abstract: Image 1 Highlights: Living close to surface coal mining sites was associated with elevated PAH exposures. Differences were observed for silicone wristbands and outdoor PUFs, but not indoor PUFs. Personal silicone wristbands are practical and effective for passive sampling.